Ghost anti-crossings caused by interlayer umklapp hybridization of bands in 2D heterostructures. (30th October 2020) - Graham, Abigail J; Zultak, Johanna; Hamer, Matthew J; Zolyomi, Viktor; Magorrian, Samuel; Barinov, Alexei; Kandyba, Viktor; Giampietri, Alessio; Locatelli, Andrea; Genuzio, Francesca; Teutsch, Natalie C; Salazar, Cuauhtémoc; et al.
Abstract: In two-dimensional heterostructures, crystalline atomic layers with differing lattice parameters can stack directly one on another. The resultant close proximity of atomic lattices with differing periodicity can lead to new phenomena. For umklapp processes, this opens the possibility for interlayer umklapp scattering, where interactions are mediated by the transfer of momenta to or from the lattice in the neighbouring layer. Using angle-resolved photoemission spectroscopy to study a graphene on InSe heterostructure, we present evidence that interlayer umklapp processes can cause hybridization between bands from neighbouring layers in regions of the Brillouin zone where bands from only one layer are expected, despite no evidence for Moiré-induced replica bands. This phenomenon manifests itself as 'ghost' anti-crossings in the InSe electronic dispersion. Applied to a range of suitable two-dimensional material pairs, this phenomenon of interlayer umklapp hybridization can be used to create strong mixing of their electronic states, giving a new tool for twist-controlled band structure engineering.